2006
DOI: 10.1007/s10620-005-9022-z
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Ghrelin and Pancreatic Polypeptide Responses in Gastroparesis

Abstract: Vagal nerve dysfunction has been implicated in the pathogenesis of diabetic gastroparesis, but its role in idiopathic gastroparesis remains uncertain. The increase in pancreatic polypeptide with sham feeding is often used as a measure of vagal integrity. Ghrelin has been suggested to function as an appetite-stimulating hormone from the gut to the brain acting through vagal afferent pathways. Systemic ghrelin also rises in part due to vagal efferent pathways. Alterations in ghrelin and its effects on appetite c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
39
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 35 publications
(37 reference statements)
3
39
0
Order By: Relevance
“…These findings are in accordance with a study of Gaddipati et al [14]. Those authors studied the ghrelin and pancreatic polypeptide responses in healthy subjects and patients with diabetic, idiopathic, or postsurgical gastroparesis after sham feeding as a measure of vagal integrity.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are in accordance with a study of Gaddipati et al [14]. Those authors studied the ghrelin and pancreatic polypeptide responses in healthy subjects and patients with diabetic, idiopathic, or postsurgical gastroparesis after sham feeding as a measure of vagal integrity.…”
Section: Discussionsupporting
confidence: 91%
“…Ghrelin stimulates short-term food intake, promotes gastric emptying, and regulates body weight. In patients with anorexia or post-bariatric surgery, profound changes in plasma ghrelin levels were found, suggesting that it is an important hormone in the regulation of body weight (Gaddipati et al 2006;Jürimäe et al 2007). Studies on the effects of acute or chronic exercise showed that high-intensity exercise could lower plasma ghrelin levels in rats (Ghanbari-Niaki et al 2008;Wang et al 2008;GhanbariNiaki et al 2009).…”
mentioning
confidence: 99%
“…Thus, suppression of ghrelin by food or an oral glucose load may not be regulated by the plasma level of glucose and/or insulin, but rather by some direct or indirect information from the gastrointestinal tract. Very recently, Gaddipati et al reported that sham feeding could increase the plasma ghrelin level in normal subjects, while such a response of ghrelin was not observed in patients with diabetic gastroparesis [27]. In contrast, Arosio et al reported that circulating ghrelin concentrations decreased with sham feeding as they do with actual meal ingestion in humans [28].…”
Section: Discussionmentioning
confidence: 99%